Backcasting energy saving and CO₂ emission reductions by using feebates system in Japan - Keiko Hirota; Minato Kiyoyuki; Kii Masanobu (European Regional Science Association (ERSA), 2004)
After the Kyoto Conference (COP3), the Japanese transport sector was required to reduce carbon dioxide (CO2) emissions by 16% by 2010. The Japanese government has decided to improve the fuel economy standard in 2010 by improving it by an average of 22.8%. However, Japanese consumers tend to prefer heavier passenger cars such as four-wheel drive or recreational vehicles. Because of the difficult target of COP3, environmental policy should involve not only automotive technologies but also non-technical measures. Since Japanese vehicle taxes are expensive compared to other OECD countries, we would like to introduce the “feebate”, a word composed from “fee” and “rebate”, as a “Green Tax” at the acquisition stage. The feebate system charges a fee for less fuel-efficient vehicles and refunds for vehicles more fuel efficient than the fuel efficiency standard. This system is a market based alternative by fuel efficiency standards so that it can be tax neutral. Acquisition tax does not affect to environmental sustainability. Since social marginal cost has increased more and more, it is not always realistic to impose all the costs at the motoring tax level. The feebate system could partially share the social marginal cost and might mitigate the rebound effect at the motoring stage. We use the data set from 1995-2001 on fuel efficiency by vehicle type and the fuel efficiency standards of 1995. The contribution of this paper will be to propose a combination of feebate rate and CO2 emission reduction by vehicle gross weight group.
Keywords: 330